Impact of the British Bible Society and the American Board of Commissioners for foreign missions in the Albanian cultural awakening - Ethem Çeku (Cogent Arts & Humanities)
Recent research on the history of Albanian education development has not sufficiently reflected the contribution of British and American Protestant missions. These missions aimed to translate the Bible into Albanian and promote its readership through school courses. Although the activities of the British Bible Society and the American Board were conducted in cooperation with prominent activists of the Albanian National Renaissance, this collaboration has not been clearly highlighted in existing studies. Therefore, this scientific study aims to explore the relationships, interactions, and joint commitments that influenced the cultural awakening of Albanians. By comparing the goals of Protestant missionaries and Albanian revivalists, we can discern points of convergence and divergence. Additionally, the study reveals the involvement of revivalists in the British Bible Society and the American Board of Commissioners. Recognising the contributions of Protestant missionaries, Albanian patriots sought to institutionalise cooperation with the missionaries to establish Protestant schools in the Albanian language.